Estimated impact of long‐acting injectable PrEP in South Africa: a model comparison analysis - Sarah E. Stansfield; Mia Moore; Lise Jamieson; Gesine Meyer‐Rath; Leigh F. Johnson; David Kaftan; Anna Bershteyn; Jennifer Smith; Valentina Cambiano; Loveleen Bansi‐Matharu; Andrew Phillips; Jesse Heitner; et al. (Journal of the International AIDS Society)
Abstract Introduction Long‐acting injectable cabotegravir (CAB‐LA) demonstrated superiority to daily tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) for human immunodeficiency virus (HIV) pre‐exposure prophylaxis (PrEP) in two clinical trials. This analysis projects the impact of expanding PrEP coverage with CAB‐LA in South Africa between 2022 and 2042. Methods Three independently calibrated models of HIV transmission in South Africa (Synthesis, EMOD‐HIV, Thembisa) projected HIV acquisitions and effective coverage (average PrEP coverage across exposure groups, weighted by HIV incidence in the absence of PrEP in each group) over 20 years under multiple scenarios of PrEP expansion compared to no PrEP expansion. PrEP expansion scenarios differed in targeted overall coverage, speed of expansion, coverage of high‐exposure groups, and relative coverage of women and men. Results Achieving 5% PrEP coverage with CAB‐LA by 2032 prioritizing high‐exposure groups resulted in 49% (Synthesis), 18% (EMOD‐HIV), and 8% (Thembisa) effective coverage and averted a median of 43%, 29% and 10% of new HIV acquisitions, respectively. Similar expansion with TDF/FTC resulted in lower impact by 19 percentage points (pp), 18pp and 3pp, respectively. Increasing CAB‐LA coverage to 15% led to an additional 7pp, 12pp and 16pp, respectively, of HIV acquisitions averted. Achieving 5% CAB‐LA coverage expanding to women only resulted in a lower impact by 16pp (Synthesis) and 13pp (EMOD‐HIV), and a higher impact by 2pp (Thembisa). Scenarios with similar effective coverage resulted in comparable impact estimates across models. Conclusions Offering CAB‐LA in South Africa may substantially impact the HIV epidemic based on these projections. Effective coverage proved to be a good predictor of intervention effectiveness.